Blue ocean strategy insights and experiences of Universiti Sains Malaysia - Ramli Mohamed (Penerbit Universiti Sains Malaysia, 2012)
This book provides a rich collection of illustrations, examples and applications of how the Blue Ocean Strategy works in institutions of higher education.